Who Drains Bond Market Liquidity in an Emerging Market? - Hoyos, Ricardo; Liu, Yang.; Miao, Hui.; Saborowski, Christian (Washington, D.C. : International Monetary Fund, 2020)
This paper examines the drivers of liquidity shortages in the Mexican government bond market. We use unique transaction- and quote level data with information on end-investors to construct an index of bond market liquidity. We find that liquidity remained stable in recent years, although temporary shortages arose amid domestic and global market stress. The analysis suggests that the largest liquidity squeezes have tended to be driven by foreign investors, whose sell-offs were especially pronounced in less liquid market segments. While domestic banks often absorbed part of the shock, other domestic investors-with the notable inclusion of domestic pension and mutual funds-appeared to take a more opportunistic stance depending on the nature of the shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet